2011
DOI: 10.1515/dmdi.2011.006
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of multidrug resistant proteins in refractory epilepsy and antiepileptic drugs interactions

Abstract: Epilepsy is a common neurological disorder. About one-third of epilepsy patients have a multidrug resistance (MDR) phenotype and develop refractory epilepsy (RE). Changes in the properties of the antiepileptic drugs (AEDs) targets resulting in reduced drug sensitivity, can't explain the MDR phenotype. This particular refractoriness is now attributed to overexpression of multidrug transporters in brain, leading to impaired access of AEDs to CNS targets, and it was documented in both human as well as in experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Our results might indicate another potential mechanism, namely reduced degree in calcineurin inhibitors-induced (CNI) toxicity due to the faster elimination of CNI into the proximal tubular lumen by cysteamine mediated P-gp stimulation. Whether the observed small increase in P-gp activity is clinically relevant needs to be determined, but as shown for single nucleotide polymorphisms in MDR1 leading to gain in function of P-gp, as seen for instance for MDR1 polymorphisms in epilepsia treatment [13], this might have an impact for pharmacotherapy. The increase in P-gp activity is interesting and possibly related to multiple binding sites on P-gp that are allosterically linked [14,15].…”
Section: Resultsmentioning
confidence: 99%
“…Our results might indicate another potential mechanism, namely reduced degree in calcineurin inhibitors-induced (CNI) toxicity due to the faster elimination of CNI into the proximal tubular lumen by cysteamine mediated P-gp stimulation. Whether the observed small increase in P-gp activity is clinically relevant needs to be determined, but as shown for single nucleotide polymorphisms in MDR1 leading to gain in function of P-gp, as seen for instance for MDR1 polymorphisms in epilepsia treatment [13], this might have an impact for pharmacotherapy. The increase in P-gp activity is interesting and possibly related to multiple binding sites on P-gp that are allosterically linked [14,15].…”
Section: Resultsmentioning
confidence: 99%
“…Refractory epilepsy is a common neurologic disease that accounts for approximately one-third of epileptic patients with resistance to single or multiple drugs used for antiepileptic treatment [1,2] . Clinical studies have shown that if the first antiepileptic drug (AED) prescribed was ineffective, switching to another AED or to a combination of AEDs yielded similar negative results.…”
Section: Introductionmentioning
confidence: 99%
“…Two well-known hypotheses have emerged to explain at least part of the biological mechanism underlying drug resistance: the target hypothesis and the transporter hypotheses [71]. The target hypothesis suggests that alterations in specific drug targets results in reduction of AED sensitivity [72] and it proposes that increased expression of multidrug transporter proteins at the blood-brain barrier leads to decreased bioavailability and limited brain access of AEDs that may result in drug resistance [73].…”
Section: Pharmacogenetics Of Carbamazepine Transporters and Targetsmentioning
confidence: 99%